Ranking upper stages in low Earth orbit for active removal. (May 2016) - Anselmo, L.; Pardini, C.
Abstract: This paper addresses the problem of ranking the upper stages in orbit in order to evaluate their potential detrimental effects on the debris environment over the long-term, and the relative advantage of having them actively de-orbited. To do so, a new ranking scheme is introduced, applicable to any object in low Earth orbit (LEO) and able to prioritize the target objects potentially most critical for the future preservation of the LEO protected region. Applying the proposed approach, it was found, for instance, that the 22 most massive upper stages abandoned in LEO, at the beginning of 2015, are on the whole equivalent to several hundred average intact objects in sun-synchronous orbit, regarding their latent detrimental effects on the debris environment over the next 200 years. Most of them could therefore be the top priority targets of any worldwide coordinated effort for active removal and the prevention of new collisional debris. The ranking scheme was also applied to other main models of rocket bodies currently in orbit, trying to identify the combinations of orbital elements and upper stage types requiring particular attention. Highlights: The stages left in space were categorized in terms of number, mass and orbit. The types contributing to most of the mass and number in LEO were identified. A new ranking index was applied to assess their long-term environment criticality. The ranking obtained could also be used for active removal priority listing.